2012
DOI: 10.1242/jeb.074849
|View full text |Cite
|
Sign up to set email alerts
|

New insights from serranid fishes on the role of trade-offs in suction feeding diversification

Abstract: SUMMARYSuction feeding is central to prey capture in the vast majority of ray-finned fishes and has been well studied from a detailed, mechanistic perspective. Several major trade-offs are thought to have shaped the diversification of suction-feeding morphology and behavior, and have become well established in the literature. We revisited several of these expectations in a study of prey capture morphology and kinematics in 30 species of serranid fishes, a large, ecologically variable group that exhibits divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 67 publications
4
54
2
Order By: Relevance
“…Body ram and jaw ram can be used in combination with suction to decrease the distance between predator and prey. The amount of body ram also influences initial predator-prey distance, strike speed and strike duration, as well as the shape and volume of ingested water during the strike (Weihs, 1980;Harper et al, 1991;Higham et al, 2005;Tran et al, 2010;Oufiero et al, 2012). Jaw protrusion is the most common mechanism of jaw ram and has been shown to decrease the hydrodynamic disturbance detectable by prey while significantly increasing the suction forces on prey (Holzman et al, 2008;Holzman and Wainwright, 2009;Staab et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Body ram and jaw ram can be used in combination with suction to decrease the distance between predator and prey. The amount of body ram also influences initial predator-prey distance, strike speed and strike duration, as well as the shape and volume of ingested water during the strike (Weihs, 1980;Harper et al, 1991;Higham et al, 2005;Tran et al, 2010;Oufiero et al, 2012). Jaw protrusion is the most common mechanism of jaw ram and has been shown to decrease the hydrodynamic disturbance detectable by prey while significantly increasing the suction forces on prey (Holzman et al, 2008;Holzman and Wainwright, 2009;Staab et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The limited reach of suction has been found to lead to very little diversity in suction distance (Wainwright et al, 2001), while there is much more variation possible in ram distance (Ferry et al, 2001b;Wainwright et al, 2001;Tran et al, 2010). Instead of a straightforward continuum between ram speed and suction capacity, the diversity of suction capacity was found to be dependent on attack speed among 30 serranid species (Oufiero et al, 2012). Others have recently focused on the duration of suction and predatory movements during feeding strikes in ray-finned fishes and found that the majority of variation among strikes is driven by the duration of ram movement (Ferry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very similar case is the development of a crack in solid surfaces in response to stress (Matsuyama et al, 2010), which is a highly nonlinear and unpredictable physical process that should benefit from an automatic marking of the events for the consequent analysis of, for instance, initial crack size, its location and its speed of propagation. High-speed cameras are a common tool in the study of feeding kinematics (Ferry-Graham et al, 2002;Oufiero et al, 2012;Wainwright and Bellwood, 2002;Wainwright et al, 2007Wainwright et al, , 2001Westphal and O'Malley, 2013); they are often used to record short videos (lasting a few seconds) and the analysis is usually focused on feeding kinematics and prey response. Here, we use a digital videorecording system that is geared to collect continuous high-speed videos and facilitate the unbiased identification and isolation of behavioral events in the field of view.…”
Section: Discussionmentioning
confidence: 99%
“…A vast majority of ray-finned fishes use suction to capture elusive or loosely attached prey (Case et al, 2008;Ferry-Graham et al, 2001;Norton and Brainerd, 1993;Oufiero et al, 2012;Van Wassenbergh and De Rechter, 2011;Wainwright et al, 2007Wainwright et al, , 2001; Waltzek and Wainwright, 2003). Despite the diversity of fishes using this feeding mode, the movements leading to suction are highly conserved in teleosts (Lauder, 1985(Lauder, , 1982Sanford and Wainwright, 2002;Westneat and Wainwright, 1989).…”
Section: Introductionmentioning
confidence: 99%